Firm size, January and pre-holiday effects : existence and possible explainations in the Singapore market. - Chua, Chin Heng. (2013)
One of the dominant themes in the academic literature since the 1960s has been the concept of an efficient capital market. Efficient market hypothesis indicates that public information, be it past prices or dividend announcements, is fairly rapidly incorporated in security prices. Recently, certain apparent major irregularities have been detected in the capital markets. These irregularities have been persistent and of such a large order of magnitude that their existence could not be ignored.